Analysis of cavopulmonary and cardiac flow characteristics in fontan Patients: Comparison with healthy volunteers. Issue 6 (11th January 2019) - Rutkowski, David R.; Barton, Gregory; François, Christopher J.; Bartlett, Heather L.; Anagnostopoulos, Petros V.; Roldán‐Alzate, Alejandro
Abstract : Background: Characterizing the flow of the Fontan circuit, and correlating flow characteristics with the development of complications, is an important clinical challenge. Past work has analyzed the flow characteristics of Fontan circulation on a component‐by‐component basis. 4D flow MRI with radial projections allows for large volumetric coverage, and therefore can be used to analyze the flow through many codependent cardiovascular components in a single imaging session. Purpose: To describe flow characteristics across the entire Fontan circuit and to compare these with the flow characteristics in healthy volunteers. Study Type: Prospective. Subjects: Eleven single ventricle patients with a Fontan connection and 15 healthy controls. Sequence: Phase contrast with vastly undersampled isotropic projection reconstruction (PC‐VIPR) at a field strength of 3 T. Assessment: Cavopulmonary and ventricular flow distributions, blood flow kinetic energy, vorticities, efficiency indices, and other flow parameters were analyzed using Ensight and MatLab. Statistical Tests: The results were compared across Fontan subjects, between respiratory phases, and between Fontan subjects and healthy volunteers using a Student's t ‐test for unequal sample sizes and linear regression. Results: Cava‐specific pulmonary flow distributions of Fontan patients varied significantly between respiratory phases ( P < 0.05). Ventricular kinetic energy (KE) was significantly higher in Fontan patients than it was in healthy controls, leading to a lower cardiac efficiency metric in the Fontan group. A significant diastolic KE time‐shift was also observed in the Fontan patient group. Peak diastolic KE was significantly higher in the single ventricle of patients with right ventricle morphology than it was in left ventricle morphology patients. Data Conclusion: Radial 4D flow MRI can be used for comprehensive analysis of single ventricle Fontan flow characteristics. Level of Evidence : 2 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019.